2007
DOI: 10.1183/09031936.00092306
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of pulmonary arterial hypertension

Abstract: All hospitalisations for pulmonary arterial hypertension (PAH) in the Scottish population were examined to determine the epidemiological features of PAH. These data were compared with expert data from the Scottish Pulmonary Vascular Unit (SPVU).Using the linked Scottish Morbidity Record scheme, data from all adults aged 16-65 yrs admitted with PAH (idiopathic PAH, pulmonary hypertension associated with congenital heart abnormalities and pulmonary hypertension associated with connective tissue disorders) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
480
2
28

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 695 publications
(531 citation statements)
references
References 15 publications
21
480
2
28
Order By: Relevance
“…This value has been used for selecting patients in all RCTs and registries of PAH [3,4,8]. Recent re-evaluation of available data has shown that the normal P pa at rest is 14¡3 mmHg, with an upper limit of normal of ,20 mmHg [9,10].…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This value has been used for selecting patients in all RCTs and registries of PAH [3,4,8]. Recent re-evaluation of available data has shown that the normal P pa at rest is 14¡3 mmHg, with an upper limit of normal of ,20 mmHg [9,10].…”
Section: Definitionsmentioning
confidence: 99%
“…4. Referral centres are required to undertake a programme of clinical audit of outcomes, which will include survival analysis.…”
Section: Definition Of a Pulmonary Arterial Hypertension Referral Centrementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with pulmonary hypertension (PH) have a high mortality [1,2]. Symptoms can be subtle and there is frequently a long delay to diagnosis [1].…”
Section: Introductionmentioning
confidence: 99%
“…5 A study from Scotland, however, cited the incidence as 2.5 cases/million/yr in men and 4.0 cases/million/yr in women. 6 Any age group can be affected, but most often iPAH occurs in the third decade of life in women and fourth decade of life in men. No ethnic predisposition has been reported.…”
Section: Epidemiologymentioning
confidence: 99%